2010
DOI: 10.1038/nsmb.1892
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of quinolone inhibition of type IIA topoisomerases and target-mediated resistance

Abstract: Quinolone antibacterials have been used to treat bacterial infections for over 40 years. A crystal structure of moxifloxacin in complex with Acinetobacter baumannii topoisomerase IV now shows the wedge-shaped quinolone stacking between base pairs at the DNA cleavage site and binding conserved residues in the DNA cleavage domain through chelation of a noncatalytic magnesium ion. This provides a molecular basis for the quinolone inhibition mechanism, resistance mutations and invariant quinolone antibacterial str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
344
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 269 publications
(361 citation statements)
references
References 13 publications
15
344
0
2
Order By: Relevance
“…The residues lining the thiophene compoundbinding pocket are conserved among bacteria, perhaps because the pocket needs to open and close during the bacterial catalytic cycle, as observed when the two A. baumannii topo IV structures are compared (SI Appendix, Figs. S8 and S9) (25). This finding suggests that the opening and closing of this Aα1 hinge pocket may be coupled to the binding, cleavage, religation, and release of DNA from the DNA gate.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The residues lining the thiophene compoundbinding pocket are conserved among bacteria, perhaps because the pocket needs to open and close during the bacterial catalytic cycle, as observed when the two A. baumannii topo IV structures are compared (SI Appendix, Figs. S8 and S9) (25). This finding suggests that the opening and closing of this Aα1 hinge pocket may be coupled to the binding, cleavage, religation, and release of DNA from the DNA gate.…”
Section: Discussionmentioning
confidence: 84%
“…These structural data showed that compound 1 bound to the protein at a site remote from the DNA-cleavage site and devoid of any direct DNA contacts. As far as we know, neither of these features has been previously reported in topoisomerase II poisons (15,19,25,26). The binding pocket lies at the interface between the GyrB topoisomerase-primase (TOPRIM) domain (27) and GyrA winged helix domain (WHD) and opens as a groove toward the outer side of the enzyme (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This bridge is formed by a divalent metal ion that is chelated by the C3/C4 keto acid of the drug and stabilized by four water molecules (19). Two of these water molecules are coordinated by a conserved serine and acidic residue (located four positions downstream) in the A subunit of the enzyme.…”
Section: D94gmentioning
confidence: 99%
“…Recent structural (19) and functional (20,21) studies with topoisomerase IV indicate that quinolones interact with bacterial type II enzymes primarily through a water-metal ion bridge. This bridge is formed by a divalent metal ion that is chelated by the C3/C4 keto acid of the drug and stabilized by four water molecules (19).…”
Section: D94gmentioning
confidence: 99%